EFFECT OF COMBINATION OF YEAST (Saccharomyces cerevisae + Candida utilis) AND HERBS SUPPLEMENTATION IN FINISHING DIET ON CARCASS CHARACTERISTICS OF BEEF CATTLE - Mahyuddin, P.; Winugroho, M. (Diponegoro University, 2010)
A 75 days feeding trial was completed to study the effect of inclusion of a combined probioticyeast+herbs in finishing diet on carcass characteristics of beef cattle. Thirty bull of Ongole crossbred,age 2.5-3 years old with average body weight (BW) of 320 kg were used in this experiment. They weredivided into 2 groups, each of 15 animals and were allotted to control and treatment. They wereslaughtered at around 450 kg BW. The treated animals were given a supplementation containingcombined yeast (Saccharomyces cerevisae and Candida utilis) and herbs. All animals were fed a diet ofammoniated rice straw and commercial concentrate with a ratio of 10: 90. Addition of combinedprobiotics + herbs in the diet increased percentage of carcass, dressing and meat, but there were noeffect on live weight gain (LWG), % bone, meat:bone ratio, % body fat, back fat thickness and eyemuscle area. There was a reduction in the percentage of offal due to a decrease in intestinal weight in thetreated animal.